Phytochemistry, pharmacology, and potential clinical applications of saffron: A review. (5th December 2021) - Xing, Bingcong; Li, Shuailing; Yang, Jiaxin; Lin, Ding; Feng, Yue; Lu, Jiangjie; Shao, Qingsong
Abstract: Ethnopharmacological relevance: Saffron, the dried red stigma of the perennial herb Crocus sativus L. (Iridaceae), is one of the most important and expensive spices in the world. It is used as a traditional Chinese medicine with demonstrated effects in promoting blood circulation and suppressing blood stasis, cooling blood detoxification, and relieving depression. It is mainly used for the treatment of depression, irregular menstruation, postpartum thrombosis, and bruises. Aim of the study: This review aims to provide a systematic and up-to-date overview of the phytochemistry, pharmacology, and clinical applications of saffron. We hope it could provide useful references and guidance for the future directions of research on saffron. Materials and methods: The online database, such as Web of Science, Google Scholar, Science Direct, PubMed, SpringerLink, Wiley Online Library, SciFinder and Chemical book, and CNKI were used to collect relevant literature. And the classic books about Chinese herbal medicine were also being referenced. Results: More than 150 chemical compounds, including carotenoids, flavonoids and flavonoid glycosides, monoterpenes and monoterpenoid derivatives, monocyclic aromatic hydrocarbons, amino acids, alkaloids and others, were revealed. The pharmacological activities study of saffron were focused on the antioxidant, anti-inflammatory, antitumor, antidepressant, hypoglycemic, hypolipidemic, memory-enhancing, and so on. Currently, saffron is mainly used for the treatment of diabetes, Alzheimer's disease, depression, anxiety disorders, cardiovascular diseases, learning and memory disorders, cancer, and other conditions. Conclusions: Phytochemical and pharmacological analyses of saffron have been revealed in recent studies. However, clinical studies have focused mainly on AD, depression and anxiety disorders. Therefore, a large number of clinical trials are needed to study the efficacy of saffron and its major chemical components against other diseases including hypertension, hyperlipidemia, and cancer. Further studies of the mechanism of action and toxicological properties of saffron are also required, especially research to establish an effective dose of saffron and its long-term toxicity in vivo . Graphical abstract: Image 1